2013
DOI: 10.1002/ajh.23566
|View full text |Cite
|
Sign up to set email alerts
|

The lymphocyte to monocyte ratio improves the IPI‐risk definition of diffuse large B‐cell lymphoma when rituximab is added to chemotherapy

Abstract: The peripheral blood lymphocyte to monocyte ratio (LMR) at diagnosis can be clinically relevant in patients with diffuse large B‐cell lymphoma (DLBCL). We reviewed the outcome of 1,057 DLBCL patients followed from 1984 to 2012 at four centers. LMR was analyzed as a clinical biomarker by receiver‐operating characteristic (ROC) analysis and Harrell's C‐statistics. Patients were characterized by a median age of 61 years, International Prognostic Index (IPI) score of >2 in 39%, and were treated with a rituximab‐co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 40 publications
(53 reference statements)
4
42
5
Order By: Relevance
“…However, the evidence in ENKTL was insufficient. 20 Rambaldi et al 22 found that ALC/AMC ratio has a strong prognostic relevance and is a risk factor from the IPI when rituximab is added to chemotherapy in diffuse large B-cell lymphoma. Similar results were shown in other cohorts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the evidence in ENKTL was insufficient. 20 Rambaldi et al 22 found that ALC/AMC ratio has a strong prognostic relevance and is a risk factor from the IPI when rituximab is added to chemotherapy in diffuse large B-cell lymphoma. Similar results were shown in other cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…1 ALC/AMC ratio was determined as recorded formerly. [21][22][23][24] ALC/AMC prognostic score was calculated in accordance with Wilcox's study. 19 In general, the patients were classified into three risk groups: low risk (normal ALC and AMC), intermediate risk (low ALC or high AMC), and high risk (low ALC and high AMC).…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Monocytes, which are considered immunologically relevant and are regarded as a surrogate marker of the tumor microenvironment, were also recently reported to be a prognostic factor in DLBCL [8-11], follicular lymphoma (FL) [12,13], T-cell lymphoma [14], extranodal natural killer/T-cell lymphoma (ENKL) [15] and Hodgkin’s Lymphoma (HL) [16,17]. Absolute lymphocyte count/absolute monocyte count ratio (ALC/AMC ratio) at diagnosis, as a simple biomarker combining an estimate of host immune homeostasis and tumor microenvironment, was recently shown to be an independent prognostic indicator in HL [16,17] and DLBCL [10,11]. However, to our best knowledge, there is no data available on whether the ALC/AMC ratio at the time of first relapse predicts outcome in patients with relapsed/primary refractory DLBCL.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Other authors have observed that the preoperative neutrophil-to-lymphocyte ratio (NLR) can be used as a prognostic marker in patients with CRC, [8][9][10] although a standard cutoff value has yet to be determined. 11,12 The lymphocyte-tomonocyte ratio (LMR) has been shown to predict for worse outcomes in patients with diffuse large B-cell lymphoma 13 and nasopharyngeal carcinoma. 14 However, its effects in patients with CRC remain undefined.…”
mentioning
confidence: 99%